HUMAN SECURITY – BUILDING THE POST-2015 DEVELOPMENT FRAMEWORK - Andreea IANCU (SEA: Practical Application of Science, 2015)

(untitled)
This article approaches the post-2015 Millennium Development Goals agenda through the human security paradigm. It suggests that the human security paradigm represents “the missing link” from the development agenda. Therefore, this analysis explains the necessity for extending the development agenda by including the human security doctrine. The first part of the article discusses the relation between human security and development. The next section analyzes the values of the Millennium Declaration and the Millennium Development Goals. The last part evaluates the improvements that the inclusion of the human security on the post-2015 development framework may bring. The results of this analysis present illustrate the opportunity of deepening the MDGs agenda with a more realistic and ethical approach, through the inclusion of the human security paradigm within the development agenda.